(untitled) (Al-Aasar, 2025)
The COVID-19 pandemic has dramatically transformed the landscape of organizational behavior, particularly in developing economies such as Pakistan. With businesses forced to adapt to remote operations and digital infrastructure, a noticeable shift has emerged in employee attitudes, workplace culture, and managerial expectations. This study examines the evolving dynamics of organizational behavior in Pakistan’s post-pandemic corporate and service sectors, focusing on areas such as employee flexibility, virtual communication norms, leadership responsiveness, and trust-based management. Using a literature-based approach, the paper synthesizes key insights from contemporary studies and global reports to outline how behavioral expectations have changed on both the employee and employer sides. It highlights the increased dependence on technology, the importance of emotional intelligence in leadership, and the rising emphasis on work-life balance and employee well-being. The findings suggest that for organizations to thrive in this new normal, they must embrace adaptive behavior, inclusive culture, and technology-driven practices. This paper serves as a useful guide for HR professionals, managers, and policymakers looking to align their post-pandemic strategies with the emerging realities of workplace behavior and employee engagement in Pakistan.